1977
DOI: 10.3109/03009747709095451
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up of90Yttrium-Treated Knee-Joint Arthritis

Abstract: The results are reported of the treatment of 33 patients with long-standing, therapy-resistant synovitis and effusion of the knee by intra-articular injection of 90Yttrium. In 25 patients with bilateral gonitis the effect of the treatment was compared with the effect of local corticosteroid therapy to the contralateral knee. The irradiated group showed statistically significantly better therapeutic results at 3, 6, and 12 months and the effect weakened in proportion to the length of the follow-up period. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 8 publications
1
10
0
3
Order By: Relevance
“…Szanto [30] demonstrated a significant benefit of Y-90 compared to intra-articular methylprednisolone (59 vs. 14% improved at 12 months after therapy, P \ 0.01). The ARC trial [31], comparing Y-90 and intra-articular triamcinolone hexacetonide, was terminated prematurely because of recruitment problems.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Szanto [30] demonstrated a significant benefit of Y-90 compared to intra-articular methylprednisolone (59 vs. 14% improved at 12 months after therapy, P \ 0.01). The ARC trial [31], comparing Y-90 and intra-articular triamcinolone hexacetonide, was terminated prematurely because of recruitment problems.…”
Section: Discussionmentioning
confidence: 90%
“…There are three controlled studies comparing RSO using Y-90 to intra-articular steroids alone [30][31][32]. Szanto [30] demonstrated a significant benefit of Y-90 compared to intra-articular methylprednisolone (59 vs. 14% improved at 12 months after therapy, P \ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of 62 knee joints controlled by X-ray showed a subpatellar calcification; 12 of these cases had a homogeneous intra-articular distribution in the scintigraphic control whereas two showed a hot spot [13]. DISCUSSION Previous studies have demonstrated the efficacy of radiation synovectomy with Y90 and the statistically significant superiority of Y90 to saline, non-radioactive yttrium and corticosteroids [14,15] in the treatment of the large and medium sized joints in RA, PsA and OA [16,18].…”
Section: Resultsmentioning
confidence: 94%
“…Radiosynovectomy has been used since 1952, and the radionuclide yttrium-90 has been preferred for knee radiosynovectomies since the 1970s, due to strong β radiation and little γ-radiation. It has been diffi cult to evaluate the technique using double-blind clinical trials, although two trials show superiority of yttrium-90 knee radiosynovectomy over intra-articular triamcinolone [ 86 ] or methylprednisolone acetate [ 87 ]. Indications for radiosynovectomy include rheumatoid arthritis, other forms of chronic infl ammatory arthritis like psoriatic arthritis or ankylosing spondylitis with peripheral joint involvement, haemophilic synovitis and infl ammatory osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%